A Qualitative Study Exploring Perception and Health Behaviors Related to Sarcopenic Obesity among Thai Older Adults in Rural Community - Samaisong, Nuchthida; Somprasert, Chomchuen; Pawloski, Lisa (The Journal of Behavioral Science, 2024)
Background/ problem: Sarcopenic obesity (SO) is a condition characterized by the coexistence of obesity and sarcopenia. The prevalence of SO is significantly high among seniors; a trend exacerbated by a global rise of aging populations and obesity rates. Thailand has one of the fastest aging populations in the world, and it is not immune to rise in obesity, with 38.4% of seniors being obese. Objective/ purpose: This study explores the perceptions and health behaviors related to SO among older adults in rural communities in Thailand. Design and Methodology: A qualitative descriptive research was used. Participants were selected through purposive and snowball sampling techniques. In-depth interviews were conducted from 25 older adults with SO. Data were transcribed verbatim and continued until data saturation was achieved. The data were verified from focus group discussions with 12 participants. Data were analyzed using content analysis. Findings: The findings reveal that SO is largely unknown among Thai seniors, leading to poor awareness and symptom management. Many participants had chronic diseases that could improve with SO management. Contributing factors include excessive energy intake, insufficient protein consumption, low physical activity, lack of resistance exercise, and family encouraging unhealthy behavior. Conclusion and Implications: The findings offer valuable insight for developing behaviors modification strategies including raising SO awareness and encouraging SO health literacy.